Shifting knowledge practices for sustainable land use: Insights from producers of Aotearoa New Zealand - Kirk, Nicholas; Duncan, Ronlyn; Booth, Pamela; Robson-Williams, Melissa (Frontiers in Agronomy, 2022)
Governments have been introducing regulations alongside sustainability-focused incentives, programs, and policies to help address environmental issues associated with agriculture. In this new ecological and policy context, where the socio-economic consequences of environmental limits are beginning to be experienced, old questions are being asked about how agricultural producers engage with advice and advisors and what factors might facilitate a faster transition to more sustainable land use. This paper presents research from Aotearoa New Zealand where a nationwide survey and focus groups have examined how producers are using advisory services. The research draws on the ‘triggering change’ cycle to explain how imperatives to shift to more sustainable land use are changing the knowledge practices of producers and their relationships with farm advisors. The research highlights the importance of conceiving producers as curators of advice and information rather than mere recipients, which involves doing their own research to identify what role they want an advisor to play. These findings have important implications for the development of future extension programmes to help producers adopt, adapt and/or co-design more sustainable land use practices.